Effect of precursors on the morphology and surface area of LaFeO3. Issue 6 (15th April 2019) - Sharma, Neeru; Sharma, S.K.; Sachdev, K.
Abstract: Surface area and morphology of materials play an important role on their gas sensing performance because of the varying number and nature of adsorption sites. Current work reports a comparative study of LaFeO3 synthesized by the facile hydrothermal method using two precursors; citric acid and KOH. The microstructure observed through FESEM and TEM showed different morphologies for the two precursors and calcination time (2 h & 6 h). Prior to calcination, higher surface area (50.54 m 2 /g) was obtained for LaFeO3 prepared using KOH as compared to that for LaFeO3 using citric acid (3.21 m 2 /g). Surface area increased from 3.21 to 7.06 m 2 /g for citric acid and decreased from 50.54 to 11.42 m 2 /g for KOH as calcination takes place for 6 h. Needle-shaped morphology of p-type LaFeO3 with high surface area (50.54 m 2 /g) for KOH would provide large active sites which would enhance sensitivity towards gases. Hence, LaFeO3 samples prepared using KOH with and without calcination are expected to give better performance for gas sensing than LaFeO3 samples synthesized using citric acid. Graphical abstract: fx1